The functional dissection of the plasma corona of SiO2-NPs spots histidine rich glycoprotein as a major player able to hamper nanoparticle capture by macrophages. Issue 42 (9th October 2015) - Fedeli, Chiara; Segat, Daniela; Tavano, Regina; Bubacco, Luigi; De Franceschi, Giorgia; de Laureto, Patrizia Polverino; Lubian, Elisa; Selvestrel, Francesco; Mancin, Fabrizio; Papini, Emanuele
Abstract : One protein, histidine rich glycoprotein, prevails in the corona of SiO2 -NPs in excess human plasma and interferes with macrophage capture. Abstract : A coat of strongly-bound host proteins, or hard corona, may influence the biological and pharmacological features of nanotheranostics by altering their cell-interaction selectivity and macrophage clearance. With the goal of identifying specific corona-effectors, we investigated how the capture of amorphous silica nanoparticles (SiO2 -NPs; Ø = 26 nm; zeta potential = −18.3 mV) by human lymphocytes, monocytes and macrophages is modulated by the prominent proteins of their plasma corona. LC MS/MS analysis, western blotting and quantitative SDS-PAGE densitometry show that Histidine Rich Glycoprotein (HRG) is the most abundant component of the SiO2 -NP hard corona in excess plasma from humans (HP) and mice (MP), together with minor amounts of the homologous Kininogen-1 (Kin-1), while it is remarkably absent in their Foetal Calf Serum (FCS)-derived corona. HRG binds with high affinity to SiO2 -NPs (HRG K d ∼2 nM) and competes with other plasma proteins for the NP surface, so forming a stable and quite homogeneous corona inhibiting nanoparticles binding to the macrophage membrane and their subsequent uptake. Conversely, in the case of lymphocytes and monocytes not only HRG but also several common plasma proteins can interchange in this inhibitory activity. The depletion of HRG and Kin-1 from HP or their plasma exhaustion by increasing NP concentration (>40 μg ml −1 in 10% HP) lead to a heterogeneous hard corona, mostly formed by fibrinogen (Fibr), HDLs, LDLs, IgGs, Kallikrein and several minor components, allowing nanoparticle binding to macrophages. Consistently, the FCS-derived SiO2 -NP hard corona, mainly formed by hemoglobin, α2 macroglobulin and HDLs but lacking HRG, permits nanoparticle uptake by macrophages. Moreover, purified HRG competes with FCS proteins for the NP surface, inhibiting their recruitment in the corona and blocking NP macrophage capture. HRG, the main component of the plasma-derived SiO2 -NPs' hard corona, has antiopsonin characteristics and uniquely confers to these particles the ability to evade macrophage capture.